Usability of electronic health record systems in UK EDs. Issue 6 (3rd March 2021) - Bloom, Benjamin Michael; Pott, Jason; Thomas, Stephen; Gaunt, David Ramon; Hughes, Thomas C
Abstract : Background: The large volume of patients, rapid staff turnover and high work pressure mean that the usability of all systems within the ED is important. The transition to electronic health records (EHRs) has brought many benefits to emergency care but imposes a significant burden on staff to enter data. Poor usability has a direct consequence and opportunity cost in staff time and resources that could otherwise be employed in patient care. This research measures the usability of EHR systems in UK EDs using a validated assessment tool. Methods: This was a survey completed by members and fellows of the Royal College of Emergency Medicine conducted during summer 2019. The primary outcome was the System Usability Scale Score, which ranges from 0 (worst) to 100 (best). Scores were compared with an internationally recognised measure of acceptable usability of 68. Results were analysed by EHR system, country, healthcare organisation and physician grade. Only EHR systems with at least 20 responses were analysed. Results: There were 1663 responses from a total population of 8794 (19%) representing 192 healthcare organisations (mainly UK NHS), and 25 EHR systems. Fifteen EHR systems had at least 20 responses and were included in the analysis. No EHR system achieved a median usability score that met the industry standard of acceptable usability. The median usability score was 53 (IQR 35–68). Individual EHR systems' scores ranged from 35 (IQR 26–53) to 65 (IQR 44–80). Conclusion: In this survey, no UK ED EHR system met the internationally validated standard of acceptable usability for information technology.